2018
DOI: 10.3390/molecules23123062
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Drug Recognition by Drug Transporters

Abstract: Drug transporters mediate the absorption, tissue distribution, and excretion of drugs. The cDNAs of P-glycoprotein, multidrug resistance proteins (MRPs/ABCC), breast cancer resistance protein (BCRP/ABCG2), peptide transporters (PEPTs/SLC15), proton-coupled folate transporters (PCFT/SLC46A1), organic anion transporting polypeptides (OATPs/SLCO), organic anion transporters (OATs/SLC22), organic cation transporters (OCTs/SLC22), and multidrug and toxin extrusions (MATEs/SLC47) have been isolated, and their functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…They are distributed in many tissues, but mainly act in the kidney (25). In the kidney, they are expressed in the basal lateral membrane of renal tubular epithelial cells (26,27), which promote the uptake of MTX from blood into renal tubular epithelial cells and mediate the urine excretion of MTX (28,29). Previous studies have shown that puerarin can inhibit the renal excretion of MTX by inhibiting the expression of OAT1/3, resulting in increased plasma MTX level (7).…”
Section: Discussionmentioning
confidence: 99%
“…They are distributed in many tissues, but mainly act in the kidney (25). In the kidney, they are expressed in the basal lateral membrane of renal tubular epithelial cells (26,27), which promote the uptake of MTX from blood into renal tubular epithelial cells and mediate the urine excretion of MTX (28,29). Previous studies have shown that puerarin can inhibit the renal excretion of MTX by inhibiting the expression of OAT1/3, resulting in increased plasma MTX level (7).…”
Section: Discussionmentioning
confidence: 99%
“…Enantioselectivity is not expected during passive absorption of enantiomers; however, it may occur when a transport-mediated process is involved [ 14 ]. The peptide transporter PEPT1 is one of the most studied drug transporters in the intestine, as it helps to improve the absorption of previously poorly absorbed drugs, which makes it a target molecule [ 15 ]. Another well-studied transporter is the proton-coupled folate transporter (PCFT), which is located on the enterocyte membrane and is responsible for mediating folate absorption.…”
Section: Enantioselectivity In Drug Pharmacokineticsmentioning
confidence: 99%
“…Bioactive chiral compounds are structurally similar, but they can exhibit different biological activity and even potency [1,2]. A classic example is thalidomide, which has a therapeutic R -isomer and a teratogenic S -isomer.…”
Section: Introductionmentioning
confidence: 99%